Strategy For Strengthening Village Credit Institutions (LPD) in Realizing Community Welfare in Sibetan Village, Bebandem District, Karangasem Regency Post Pandemi - I Nyoman Sukandia; Anak Agung Istri Agung (Law Doctoral Community Service Journal, 2022)
The growth and development of the LPD requires Human Resources with sufficient and adequate quality education, and an element of prudence is urgently needed in disbursing credit, because the credit disbursed is derived from public funds collected in the form of Savings and Time Deposits; However, even though the LPD is already in the form of a Business Entity, the responsibility is still the responsibility of the Indigenous Village community as the communal owner of the Business Entity, and does not yet have a mechanism to provide special guarantees for owners of capital/money from the community as owners of deposits in all LPDs. LPDs in Bali, as is the case with LPDs which require material guarantees to be specifically guaranteed as a form of prudence. So when faced with certain situations such as the Covid 19 pandemic; then it is not impossible for the LPD to experience liquidity problems because many loans disbursed are not smooth and even jammed, and on the other hand, the community draws a lot of Savings and Deposits for their living needs, both those that have not been and those that are due. In addition, the lack of prudence and lack of understanding of good governance have an impact on very serious problems such as losses and even bankruptcy. This study empirically examines the developments and problems of Village Credit Institutions (LPD) as a result of the Covid-19 pandemic, and takes visionary steps or strategies to strengthen the management of Village Credit Institutions (LPDs) that are resilient in realizing community welfare in Sabetan Village, Bebandem District. , Karangasem Regency Post Pandemic.